23-8x+7=60-90

Simple and best practice solution for 23-8x+7=60-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23-8x+7=60-90 equation:


Simplifying
23 + -8x + 7 = 60 + -90

Reorder the terms:
23 + 7 + -8x = 60 + -90

Combine like terms: 23 + 7 = 30
30 + -8x = 60 + -90

Combine like terms: 60 + -90 = -30
30 + -8x = -30

Solving
30 + -8x = -30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -8x = -30 + -30

Combine like terms: 30 + -30 = 0
0 + -8x = -30 + -30
-8x = -30 + -30

Combine like terms: -30 + -30 = -60
-8x = -60

Divide each side by '-8'.
x = 7.5

Simplifying
x = 7.5

See similar equations:

| 6z-2=9 | | 13=-5v-2 | | 7z+15+8u= | | .75-2.625x=3.9x | | 5y=15x-20 | | -2(34-7)=56 | | 1.2x-0.91=0.8x+2.29 | | 8-2x=15+5x | | T^2=2-6t | | -18=2n-2 | | (cos^2)x+4cosx-3=0 | | 0.2x=0.3(x+5) | | 4d-2.50=21.50 | | 6-3(1-5n)=22 | | -33=-4p+3 | | -2x^2-4=8x | | 7x-2=8x+8 | | 7x-8+4x-4=142 | | 97.6+10= | | 8.5+-2.7k=3.9k+-18.89 | | 10r+-r+-10r=11 | | 3z+6-(4z+9+8u)= | | x+108=156 | | x+x=152 | | 4x+8=x+41 | | y=0.75+0.25 | | 2*9+25*2= | | 35+13x=35x | | 4(6-3a)=3(-4a+8) | | 45=3(3x-6) | | -14+4(2x+7)-x=42 | | x+(2x+6)=126 |

Equations solver categories